Analysis of Politeness Maxims on the Youtube Channel: Jess no Limit - Hanni Pahiratunisa; Intan Sari Ramdhani (CV. Rayyan Dwi Bharata, 2023)
Humans are creatures that need each other, to interact humans need language as an intermediary. Speaking well can have a good effect on the other person. Politeness is prioritized which must be instilled in humans. As time goes by, technology is getting more sophisticated, therefore speaking or communicating with other humans can already be done through social media. Especially social media Youtube, there is often interaction between users and viewers. Therefore, the researcher is interested in conducting a study entitled